Unlawful Act Claims in Land Auction Disputes: A Juridical Analysis of Court Decision No. 29/Pdt.G/2025/PN Kwg - Gunawan Gunawan; Abu Nawas; Muh Nasir (BULETIN ADALAH, 2026)
Disputes arising from land auctions frequently involve claims of unlawful acts (perbuatan melawan hukum), particularly where alleged violations of legal rights occur during the auction process. However, not all contested auctions meet the legal threshold for liability under Article 1365 of the Indonesian Civil Code. This study addresses this issue by examining the juridical basis of unlawful act claims and the judicial reasoning applied in Court Decision No. 29/Pdt.G/2025/PN Kwg. This research employs a normative legal method using statutory, case, and conceptual approaches. Legal materials, including primary, secondary, and tertiary sources, are analyzed qualitatively to assess the legal standards governing land auction disputes. The findings demonstrate that unlawful act claims in land auction disputes require the fulfillment of key elements: an unlawful act, fault, damage, and causality. The court, in the examined decision, emphasized both procedural and substantive legality, including the validity of the auction object, the authority of auction officials, and the protection of affected parties. The ruling highlights that compliance with established legal procedures serves as a critical benchmark in determining the absence of unlawful conduct. This study contributes to clarifying the limits of civil liability in auction-related disputes and underscores the importance of legal certainty in auction practices. Keywords: Unlawful Act, Land Auction Dispute, Juridical Analysis, Court Decision, Civil Liability.